Microblading and the Science Behind it - Marwah, Manjot Kaur (Indian Dermatol Online J, 2021)
Eyebrows have been known to be an importance aspect of facial aesthetics and eyebrow restoration is now a part of anti-ageing procedures too. Microblading is a new technique in the field of permanent cosmetics for eyebrow restoration. Currently, it is one of the most sort after treatment in aesthetic procedures due to the curiosity and awareness raised by social media. Microblading is a form of superficial micropigmentation, wherein pigment is deposited till the papillary dermis, with the help of a manual device and a blade consisting of stacked needles. The resultant crisp, discrete hair like incisions simulate the eyebrow hair to give a natural look. The results are semi-permanent and last only 12-18 months. In the recent years, with the advancement in the instrumentation of microblading there have been several modifications in this procedure. Microblading has now found its applications not only in cosmetic treatments but also in dermatological conditions such as alopecia totalis, hypothyroidism, chemotherapy induced madarosis etc. It is a vital tool in any dermatology or cosmetic practise for its extensive applications. But with the rise in popularity of microblading, there is also a rise of untrained professionals performing it leading to a rise in its side-effects. This article aims at not only guiding on the instrumentation and procedure of microblading but also its pre and post procedure care, interaction with other aesthetic procedures and treating its complications.